DIGITAL ENVIRONMENTS AND THE FADING OF THE PRODUCTION-CONSUMPTION DICHOTOMY: PROSUMPTION AS A COMPREHENSIVE APPROACH - Davide Dusi (Innovative Issues and Approaches in Social Sciences, 2015)
The recent changes regarding user’s role and agency in digital environments, and the consequent influence of emerging socio-technical arrangements on productive paradigms, challenged our traditional separation between production and consumption. Productive paradigms in digital worlds proved the notion of the user as a simple consumer to be outdated. They questioned the production-consumption dichotomy and urged scholars to develop new approaches to investigate the fading of the historical separation of these two concepts. This fostered the exploration and development of new paths of research. Several concepts have been created and used to analyze current productive paradigms and the role of the users. Nevertheless, most of them seem to fail in their attempt to give a clear account of the emerging phenomena and to reach a broad understanding of all the involved actors and practices that are affecting the traditional production-consumption division. Notwithstanding the criticisms of many perspectives, the theorization of the user as prosumer – producer and consumer at the same time – and the related concept of prosumption, seems a more comprehensive approach to investigate the current ontological status of users as well as productive paradigms in digital environments. However, this theorization is in need of revision and further development.